Understanding pain in modern society: insights from attitudes to pain in the Medieval Period - Paley, Emma G.; Johnson, Mark I.; Paley, Carole A. (Frontiers in Pain Research, 2023)
Historical records provide knowledge about the way people lived in the past. Our perspective is that historical analyses of the Medieval Period provide insights to inform a fuller understanding of pain in the present era. In this article, we appraise critiques of the writings of people living with pain during the mid (high) to late Medieval Period (c. 1,000–1,500 AD) to gain insights into the nature, attitudes, lived experience, and sense-making of pain. In the Medieval Period, pain was understood in terms of Galen's four humours and the Church's doctrine of pain as a “divine gift”, “punishment for sin” and/or “sacrificial offering”. Many treatments for pain were precursors of those used in modern time and society considered pain to be a “shared experience”. We argue that sharing personal stories of life is a fundamental human attribute to foster social cohesion, and that nowadays sharing personal stories about pain is difficult during biomedically-focussed time-constrained clinical consultations. Exploring pain through a medieval lens demonstrates the importance of sharing stories of living with pain that are flexible in meaning, so that people can connect with a sense of self and their social world. We advocate a role for community-centred approaches to support people in the creation and sharing of their personal pain stories. Contributions from non-biomedical disciplines, such as history and the arts, can inform a fuller understanding of pain and its prevention and management.